Highly flexible silica/chitosan hybrid scaffolds with oriented pores for tissue regeneration - Wang,D; Romer,F; Connell,L; Walter,C; Saiz,E; Yue,S; Lee,PD; McPhail,DS; Hanna,JV; Jones,JR (Journal of Materials Chemistry B, 2015)
Inorganic/organic sol–gel hybrids have nanoscale co-networks of organic and inorganic components that give them the unique potential of tailored mechanical properties and controlled biodegradation in tissue engineering applications. Here, silica/chitosan hybrid scaffolds with oriented structures were fabricated through the sol–gel method with a unidirectional freeze casting process. 3-Glycidoxypropyl trimethoxysilane (GPTMS) was used to obtain covalent inorganic/organic coupling. Process variables were investigated such as cooling rate, GPTMS and inorganic content, which can be used to tailor the mechanical properties and hybrid chemical coupling. Structural characterization and dissolution tests confirmed the covalent cross-linking of the chitosan and the silica network in hybrids. The scaffolds had a directional lamellar structure along the freezing direction and a cellular morphology perpendicular to the freezing direction. Compression testing showed that the scaffolds with 60 wt% organic were flexible and elastomeric perpendicular to the freezing direction whilst behaving in an elastic-brittle fashion parallel to the freezing direction. The compressive strengths are about one order of magnitude higher in the latter direction reaching values of the order of 160 kPa. This behaviour provides potential for clinicians to be able to squeeze the materials to fit tissue defect sites while providing some mechanical support from the other direction.